Extensive HLA-driven viral diversity following a narrow-source HIV-1 outbreak in rural China - Dong, T; Zhang, Y; Xu, K; Yan, H; James, I; Peng, Y; Blais, M; Gaudieri, S; Chen, X; Lun, W; Wu, H; Qu, W; et al. (2011)
Obstacles to developing an HIV-1 vaccine include extensive viral diversity and lack of correlates of protective immunity. High mutation rates allow HIV-1 to adapt rapidly to selective forces such as antiretroviral therapy and immune pressure, including HIV-1-specific CTLs that select viral variants which escape T-cell recognition. Multiple factors contribute to HIV-1 diversity, making it difficult to disen-tangle the contribution of CTL selection without using complex analytical approaches. We describe an HIV-1 outbreak in 231 former plasma donors in China, where a narrow-source virus that had contaminated the donation system was apparently transmitted to many persons contemporaneously. The genetic divergence now evident in these subjects should uniquely reveal how much viral diversity at the population level is solely attributable to host factors. We found significant correlations between pair-wise divergence of viral sequences and HLA class I genotypes across epitope-length windows in HIV-1 Gag, reverse transcriptase, integrase, and Nef, corresponding to sites of 140 HLA class I allele-associated viral polymorphisms. Of all polymorphic sites across these 4 proteins, 24%-56% were sites of HLA-associated selection. These data confirm that CTL pressure has a major effect on inter-host HIV-1 viral diversity and probably represents a key element of viral control. © 2011 by The American Society of Hematology.